2002
DOI: 10.1094/mpmi.2002.15.10.990
|View full text |Cite
|
Sign up to set email alerts
|

Potato spindle tuber viroid Strains of Different Pathogenicity Induces and Suppresses Expression of Common and Unique Genes in Infected Tomato

Abstract: Viroids are the smallest plant pathogens. These RNAs do not encode proteins and are not encapsidated, and yet they can replicate autonomously, move systemically, and cause diseases in infected plants. Notably, strains of a viroid with subtle differences in nucleotide sequences can cause dramatically different symptoms in infected plants. These features make viroids unique probes to investigate the role of a pathogenic RNA genome in triggering host responses. We conducted a comprehensive analysis of the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 76 publications
8
92
0
7
Order By: Relevance
“…Most studies have been limited to analyses of viroid structure and general plant symptoms (Schnölzer et al, 1985;Owens, 1990;Owens et al, 1991Owens et al, , 1995Owens et al, , 1996Hammond, 1992;Schmitz and Riesner, 1998). Changes in the global gene expression patterns of infected plants also have been described (Itaya et al, 2002). In general, however, we have little knowledge of how a specific PSTVd sequence or structure can evoke distinct changes in host gene expression that lead to alterations in specific cellular processes and the development of particular symptoms.…”
Section: S ćmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have been limited to analyses of viroid structure and general plant symptoms (Schnölzer et al, 1985;Owens, 1990;Owens et al, 1991Owens et al, , 1995Owens et al, , 1996Hammond, 1992;Schmitz and Riesner, 1998). Changes in the global gene expression patterns of infected plants also have been described (Itaya et al, 2002). In general, however, we have little knowledge of how a specific PSTVd sequence or structure can evoke distinct changes in host gene expression that lead to alterations in specific cellular processes and the development of particular symptoms.…”
Section: S ćmentioning
confidence: 99%
“…The global gene expression pattern in an infected host has been examined by microarray analysis during viral infection (Whitham et al, 2003) and by macroarray analysis during viroid infection (Itaya et al, 2002). In general, there is a lack of understanding of how the altered expression of a partic- The number in each case is the mean Ϯ SE calculated from cell counts obtained from four complete transverse sections of the internode.…”
Section: The Possibility Of Linking Viroid Structure Host Gene Exprementioning
confidence: 99%
“…PSTVd may interact with a double-stranded RNA-activated protein kinase to disturb cellular functions leading to diseases (Diener et al, 1993). Recent studies have demonstrated comprehensive alteration in host gene expression during PSTVd infection (Itaya et al, 2002). Altered expression of certain genes can be linked to specific defects in cellular processes that lead to a particular symptom (Qi and Ding, 2003).…”
Section: Implications Of the Intranuclear Localization Of Viroid Rnasmentioning
confidence: 99%
“…Viroids are self-replicating RNAs that infect plants. They can alter the expression of selective plant genes important to growth and development (Itaya et al, 2002;Qi and Ding, 2003). A viroid genome consists of a single-stranded, covalently closed circular, noncoding, and nonencapsidated RNA, with genome sizes ranging from 275 to 400 nucleotides (Hull, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Viroid infection, which entails replication and movement, may interfere with the host regulation machinery and induce wide modifications in host gene expression (Itaya et al, 2002) that ultimately lead to the onset of macroscopic symptoms. Although downregulation of a specific tomato (Solanum lycopersicum) gene involved in cell expansion has been correlated with the stunting phenotype induced by severe PSTVd strains (Qi and Ding, 2003a), the primary molecular event has not been identified.…”
Section: Introductionmentioning
confidence: 99%